Sustainable Urban Transport: The Role of Public Transportation Quality in Reducing Private Vehicle Dependence - Arif Fakhrudin Fakhrudin; Yasmudi; Irfan Abdulhafizh Karnaen; Vidyana Mandrawaty; Indriyana Mandraeny; Prasetyowati (Sekolah Tinggi Teknologi Kedirgantaraan, 2026)
Sustainable urban transport has become a critical priority for cities worldwide as rapid urbanization and increasing mobility demand intensify traffic congestion, environmental pollution, and energy consumption. One of the major challenges faced by urban transportation systems is the growing dependence on private vehicles, which contributes significantly to greenhouse gas emissions and urban mobility inefficiencies. In response to these challenges, improving public transportation systems has been widely recognized as an essential strategy for promoting sustainable urban mobility. This study examines the role of public transportation quality in reducing private vehicle dependence among urban commuters. Using a quantitative research approach, data were collected from 312 urban commuters through a structured questionnaire survey. The study employed Structural Equation Modelling (SEM) to analyse the relationship between perceived public transportation quality and private vehicle dependence. Public transportation quality was measured through several dimensions, including reliability, accessibility, comfort, safety, and service frequency. The results indicate that public transportation quality has a significant negative effect on private vehicle dependence. This finding suggests that improvements in service quality can encourage commuters to shift from private vehicles to public transportation. In particular, reliable and accessible services, along with improved passenger comfort and safety, play a crucial role in shaping transportation mode choices. This study contributes to the literature on sustainable urban mobility by providing empirical evidence that enhancing public transportation quality can effectively reduce reliance on private vehicles. The findings also offer important policy implications for urban planners and transportation authority’s seeking to develop more sustainable and efficient urban transportation systems.